Impact of Informal Activities on Public Secondary School in Ogbomoso, Nigeria - Odunola, Olaitan Olutayo; Akinyode, Babatunde Femi (Advances in Social Sciences Research Journal, 2019)
Secondary education plays important roles in educational system and serves as link between primary and tertiary education for children to acquire additional knowledge, skills and qualities beyond their primary school level. However, informal activities surround majority of secondary schools in developing nations. Although, informal activities have lot of benefits especially in the areas of employment opportunities and income generation. Nevertheless, this study hypothesize that, the activities generate varieties of social, educational and psychological effects on secondary schools. This study employed quantitative technique through questionnaire administration and qualitative techniques through direct observation and personal interview for data collection within five selected senior secondary schools among 281 respondents. Quantitative data were analyzed by descriptive statistics, chi-square tests and development of Informal Activities Effect Index (IAEI). On the other hand, qualitative data used content analysis for analysis. The analysis were to assess the impact of informal activities on the public secondary schools. The result reveals that men of middle age majorly engaged in informal activity as possible avenue for employment opportunity and poverty alleviation strategy. However, their location have greater impact on students’ academic performance and becomes nuisance to the public secondary schools environment. The authors suggest enforcement of discipline to maintain educational standard, fencing of the school’s environment and employment of food vendors to prevent sneaking out of students during the school hours. The effectiveness of planning officers at local and state government levels for proper design and implementation of the development plan is inevitable for appropriate development control.